High Voltage Carbon‐Based Cathodes for Non‐Aqueous Aluminium‐Ion Batteries** - Dr. Shalini Divya; Prof. Thomas Nann (ChemElectroChem)
Abstract Four different forms of carbon: activated carbon (AC) from human hair, AC from hemp fibers, a carbon fullerene extract consisting of C60 and C70 fullerene (CFEx) and Super‐P carbon black were tested and compared as cathodes for non‐aqueous aluminium‐ion batteries (AIBs). These materials differ in their general structure, porosity and morphology. Fullerenes display a crystalline structure, whereas hemp fibers, Super‐P and hair are amorphous in nature. Of all materials, AC obtained from hair recorded the highest specific capacity after 50 cycles at 103 mAh g−1 with a Coulombic efficiency of ∼90 % at a current rate of 50 mA g−1. Both hemp fibers and Super‐P achieved their highest specific capacities at 56 mAh g−1 and 84 mAh g−1 respectively. CFEx recorded its highest capacity at 78 mAh g−1 and maintained it for 50 cycles. The cells were charged and discharged to 2.45 V and 0.2 V respectively.